Alternative aesthetic treatment of dental agenesis: a case report (Research, Society and Development, 2022)
Objective: To restore the self-esteem of an adolescent patient with dental agenesis through an alternative conservative aesthetic treatment. Methodology: A case report. Demarcation of the gingival plasty area and determination of bleeding points for gingivoplasty with a periodontal probe, incision using the internal bevel technique with a 15c scalpel blade and Kirkland's gingivotome. Composite resin increment technique by conditioning the enamel with 37% phosphoric acid for 30 seconds, washing with water for 1 minute and drying with absorbent paper. Application of the Adhesive System Adapter Single Bond 2 and light curing for 20 seconds. Soon after, with the aid of a Uvenner matrix, the resin Z350xt filtek supreme color B1 enamel was used for a thin veneer, photoactivated 3 times for 20 seconds. Interproximal excesses were removed with sandpaper. Results: The treatment, based on a gingivoplasty and reanatomization in composite resin, restored the patient's smile and self-esteem directly and quickly. Conclusion: A multidisciplinary planning based on the principles of conservative restorative dentistry is capable of restoring the aesthetic patterns of the smile, thus restoring the patient's self-esteem and social well-being.